Making compost from weeds: a way of management - kumar, Sushil (Indian Farming, 2018)
Weeds can be utlized for making good qulaity compost by followingscientific methods. Weeds often possess large number of seeds, which should be killed during process of composting. Pit mehod is found suitable for making compost from the weeds. Therefore, farmers are advised to use pit methods instead of NADEP method to prepare compost from the weeds.